Primary Adenocarcinoma of the Vermiform Appendix. A Case Report - Luis Antonio Revuelta Pérez; Lidia Torres Aja; Arístides Sánchez Sánchez (Universidad de las Ciencias Médicas de Cienfuegos, 2014)
Primary adenocarcinoma of the vermiform appendix is the least common carcinoma of this organ; its exact frequency is unknown. Primary malignant tumors of the appendix are rare; they are generally found in 1 to 2% of all appendices examined. Most appendiceal malignancies arise from a primary tumor in the adjacent organs, and in some cases, may be metastases from distant tumors. The case of a 43-year-old patient with a history of emergency surgery who was presumptively diagnosed with acute appendicitis is presented. The presence of an adenocarcinoma at the base of the appendix was reported by the pathology department. Because of the rarity of the condition, the publication of this case is considered scientifically important.